PENGALAMAN HIDUP PEKERJA SEKS KOMERSIAL ONLINE PADA APLIKASI MICHAT DI KABUPATEN KARAWANG - Naufal Murtadho; Tri Susanto; Nurkinan Nurkinan (Jurnal Sosial Humaniora Sigli, 2026)
The development of digital technology has transformed prostitution practices from conventional forms into online prostitution through various communication applications, one of which is MiChat. This study aimed to understand the lived experiences, motives, and life meanings of online commercial sex workers in using the MiChat application in Karawang Regency. The research employed a constructivist paradigm with Alfred Schutz’s phenomenological approach. Three online commercial sex workers were selected as informants using purposive sampling techniques. Data were collected through in-depth interviews, observations, documentation, and literature studies, and were analyzed using the Miles and Huberman data analysis model. The findings indicate that the informants’ lived experiences are influenced by economic conditions, family backgrounds, and social interactions. The motives for using MiChat are shaped by both because motives and in-order-to motives. Furthermore, the profession is interpreted as a form of life struggle, a means of achieving future goals, and a reality that must be accepted as part of life.Keywords: online prostitution, MiChat, phenomenology, lived experience, commercial sex workers